2020
DOI: 10.3390/nano10020345
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Nitrogen Doped Intercalation TiO2/TiN/Ti3C2Tx Nanocomposite Electrodes with Enhanced Pseudocapacitance

Abstract: Layered two-dimensional titanium carbide (Ti3C2Tx), as an outstanding MXene member, has captured increasing attention in supercapacitor applications due to its excellent chemical and physical properties. However, the low gravimetric capacitance of Ti3C2Tx restricts its rapid development in such applications. Herein, this work demonstrates an effective and facile hydrothermal approach to synthesize nitrogen doped intercalation TiO2/TiN/Ti3C2Tx with greatly improved gravimetric capacitance and excellent cycling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…The BE of Mn in the pure oxide (Figure 1c) is 640.7 eV, which also matches the oxidation state close to Mn 2 O 3 or Mn (III). The separation value between these two states (Mn 2p 3/2 , Mn 2p 1/2 ) of Mn is 11.64 eV, which is also consistent with the literature [4,34,35]. The BEs of 528.12 and 529.46 eV from oxygen indicate that oxygen is bonded to the metal and only a few hydroxyl groups are present (Figure 1d).…”
Section: Structural and Morphological Analysissupporting
confidence: 89%
“…The BE of Mn in the pure oxide (Figure 1c) is 640.7 eV, which also matches the oxidation state close to Mn 2 O 3 or Mn (III). The separation value between these two states (Mn 2p 3/2 , Mn 2p 1/2 ) of Mn is 11.64 eV, which is also consistent with the literature [4,34,35]. The BEs of 528.12 and 529.46 eV from oxygen indicate that oxygen is bonded to the metal and only a few hydroxyl groups are present (Figure 1d).…”
Section: Structural and Morphological Analysissupporting
confidence: 89%
“…demonstrated an effective hydrothermal approach to synthesize N‐TiO 2 /TiN/Ti 3 C 2 T x by hexamethylenetetramine. [ 204 ] It was also revealed that hexamethylenetetramine serves as both a nitrogen source and as intercalants while the Ti 3 C 2 T x itself provides the titanium element. In addition to the Ti 3 C 2 T x MXene, Yoon et al.…”
Section: Hetero‐mxenesmentioning
confidence: 99%
“…However, they have a low energy density [6]. Transition metal oxides and conductive polymers are used in pseudocapacitors owing to their high specific capacitances [7,8]. SCs experience a decrease in cycle life owing to the occurrence of the Faraday redox reaction [9].…”
Section: Introductionmentioning
confidence: 99%